Trans- and cis-resveratrol concentration in wines produced in Serbia - Đekić Sanja; Milosavljević Slobodan; Vajs Vlatka; Jović Slobodan; Petrović Aleksandar; Nikićević Ninoslav; Manojlović Verica; Nedović Viktor; Tešević Vele (Journal of the Serbian Chemical Society, 2008)
Resveratrol, which occurs in two isomeric forms, trans and cis, is a phytoalexin with numerous pharmacological activities, such as anti-cancer, antiviral, neuroprotective and anti-aging. Red wine is the main source of the compound and an easy way of including resveratrol in the human diet. In this study, the most popular commercial Serbian wines (red, white and rosé-type) were analyzed for their content of trans- and cis-resveratrol. The analysis was performed by HPLC with a UV detector. Prior to the injection, phenolic compounds were extracted onto a LiChrolut RP18 bonded silica cartridge. The concentration of trans-resveratrol ranged from 0.11 to 1.69 mg L-1 and cis-resveratrol from 0.12 to 1.49 mg L-1.